The Gleaners and I. Adelita Husni-Bey in conversation with Ana Méndez de Andes and Emilio Santiago Muíño - Méndez de Andes, Ana; Santiago Muíño, Emilio (Re-visiones, 2024)
The Gleaners and I. Adelita Husni-Bey in conversation with Ana Méndez de Andes and Emilio Santiago Muíño